2011
DOI: 10.1155/2011/860578
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of Mesenchymal Stem Cells in Liver Injury

Abstract: Mesenchymal stem cells (MSCs), represent an attractive tool for the establishment of a successful stem-cell-based therapy of liver diseases. A number of different mechanisms contribute to the therapeutic effects exerted by MSCs, since these cells can differentiate into functional hepatic cells and can also produce a series of growth factors and cytokines able to suppress inflammatory responses, reduce hepatocyte apoptosis, regress liver fibrosis, and enhance hepatocyte functionality. To date, the infusion of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 96 publications
(100 reference statements)
2
55
0
Order By: Relevance
“…New evidences of a putative differentiation of MSCs into hepatocyte-like cells have been shown in many recent publications [29] (Fig. 1).…”
Section: Plasticity: Mscs-derived Hepatocyte-like Cellsmentioning
confidence: 79%
“…New evidences of a putative differentiation of MSCs into hepatocyte-like cells have been shown in many recent publications [29] (Fig. 1).…”
Section: Plasticity: Mscs-derived Hepatocyte-like Cellsmentioning
confidence: 79%
“…Indeed, a variety of studies (Banas et al, 2007;Ishii et al, 2008;Kakinuma et al, 2009;Puglisi et al, 2011;Hang et al, 2014) have demonstrated the ability of MSCs to…”
Section: Differentiation Ability Of Mscsmentioning
confidence: 99%
“…Recently, MSCs have been isolated from a variety of tissues including umbilical cord blood, adipose tissue, liver, lung, dermis, amniotic membrane, and menstrual blood (Erices et al, 2000;Campagnoli et al, 2001;Jiang et al, 2002;de Ugarte et al, 2003;Mou et al, 2013). Additionally, MSCs can secrete a series of cytokines and signaling molecules, such as hepatocyte growth factor (HGF), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), epidermal growth factor (EGF), nitric oxide, prostaglandin E2 (PGE2), and indoleamine 2,3-dioxygenase (Ortiz et al, 2007;Kiss et al, 2008;Puglisi et al, 2011), which can regulate inflammatory responses, stimulate hepatocyte proliferation, and maintain hepatocyte function (Lin et al, 2011;Sharma et al, 2014) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest the presence of autocrine signalling, whereby the transition of stem cells into hepatocytes-like cells is induced by the secretion of Hepatocyte Growth Factor (HGF) [12,13]. In contrast, some studies postulate that paracrine signaling mediates liver regeneration through revascularization and enhancing repopulation of endogenous cells in necrotic tissue through the secretion of various cytokines and growth factors [6,14]. Stem cells may also attenuate liver fibrogenesis by inhibiting the activation of hepatic stellate cells (cells responsible for the secretion of extracellular matrix components that include collagen and adhesive glycoproteins) via stem cell-derived cytokines and growth factors such as IL6, IL10, TNFα and HGF.…”
Section: Introductionmentioning
confidence: 99%